A study on language anxiety in speaking in ESL classroom / Norhartini Aripin - Aripin, Norhartini (2010)
In Malaysian education, English is the second language (L2) where it is taught in primary and secondary schools. Eventhough speaking skill is not widely stressed out in most schools, today it is imperative to build up this skill based on the importance of the English Language in the Malaysian education system. Speaking is part of English studies where students are anxious the most during their English class. This speaking anxiety becomes a barrier in learning the language in the classroom and at the same time, it affects their performance and mostly becomes a bad sign for them to acquire the language. Speaking anxiety also influences their performance in the classroom where the students who face learning anxiety will have problems in public speaking and any other classroom activities. This study investigated the perspective of speaking anxiety in the ESL classroom and the data is gathered through an interview session with three samples and questionnaires from 200 respondents from Sekolah Menengah Kebangsaan Sri Aman, Pasir Putih, Kelantan, Sekolah Menengah Kubang Kerian 2, Kelantan and Sekolah Menengah Chukai, Kemaman. The results revealed that speaking anxiety exists as it is proven that students experience speaking anxiety in 15 out of 30 questions administered and through the interview conducted with three samples, the existence of speaking anxiety also cannot be denied.